Integrating Sharia Contracts into Digital Transactions: An Analysis of DSN-MUI Fatwas 2021 in E-Commerce Practices - Jerry Anggara Saputra; Ice Trisnawati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
The growth of e-commerce in Indonesia has created a major transformation in the digital-based buying and selling system. However, this development also raises new challenges in ensuring that transactions that occur are in accordance with sharia principles. To answer the need for sharia legal certainty in digital transactions, the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) issued Fatwa No. 144-146 of 2021 concerning hawalah, kafalah, and wakalah bil ujrah contracts. This research aims to examine the implementation of the fatwa in e-commerce practices in Indonesia and analyze its relevance to the needs of sharia-compliant digital transactions. This research uses a qualitative approach with a library research method and normative-juridical analysis. Data were collected from the DSN-MUI fatwa, fiqh muamalah literature, e-commerce regulations, and document studies from several sharia marketplace platforms in Indonesia. The results show that the understanding and application of sharia contracts in e-commerce practices are still partial, not explicit, and often not understood by industry players. Wakalah bil ujrah contracts are mostly applied in the form of platform administration fees, but kafalah and hawalah contracts are still rarely found in consumer protection mechanisms and payment systems. This study recommends the need for integration between DSN-MUI fatwas and digital regulations by relevant authorities, as well as increasing sharia literacy among digital business actors. Thus, the principles of muamalah can be fully implemented in the Islamic e-commerce ecosystem in Indonesia.